Identifikasi Kekeliruan Penggunaan Metode Statistika pada Artikel yang Dimuat di Jurnal OJS Unud - Suciptawati, Ni Luh Putu (Jurnal Matematika, 2019)
Abstract :   T he statistical method plays a role in scientific research. Use of appropriate statistical methods in analyzing  data influences research conclusions. Misuse  statistical methods will lead to incorrect conclusions. This study aims to identify the misuse of statistical methods in articles published in the OJS UNUD Journals . We reviewed 97 articles from OJS UNUD Journals published in 2017. This study  found several  misuse statistical methods these included: misuse multiple linear regression analysis, generalize conclusions based on descriptive statistics, inappropriate use of  ANOVA, misinterpretation of negative correlation values, use of Chi square test for small samples, use of t-test two samples for observations with ordinal scale Keywords : statistical methods, misuse statistical, OJS UNUD Journal